A proteção internacional do trabalho humano como resistência aos avanços do ideal político das forças do livre mercado: o “negociado sobre o legislado” na visão da OIT - Gratão, Carlos Eduardo Andrade (2024)
Law no. 13.467/2017, which implemented the so-called Labor Reform, was one of the expressions of neoliberal ideology in the country as it was guided by an interpretation of labor relations as commodities to be priced by free market forces, with minimal or even no intervention by public forces in defense of the most vulnerable party in the contractual relationship, the worker. This law gave the opposing parties, the capitalists and the workers, the power to decide their disputes based on the free disposition of their will, despite the existence of legislation protecting human labor produced under a different political aegis. This precept became known as "negotiated over legislated", possibly inspired by classical liberalism, and therefore contrary to the understanding of the International Labour Organization's (ILO) Committee on Freedom of Association and Committee of Experts on the Application of Conventions and Recommendations, whose understanding of labour relations is anchored in political and civilizational frameworks of social justice. Since the hypothesis is that this legal innovation substantially harms human rights, this research was dedicated to demonstrating that the neoliberal political ideal is contrary to social human rights in the form of decent work and that the Brazilian law is incompatible with the ILO's understanding. To this end, the research deals with neoliberalism, its way of acting against the welfare state, democracy and social human rights, by prescribing the preponderance of freedom rights and denying social justice. The research also shows that social, economic and cultural rights have the same philosophical origins as civil and political rights, and examines the justification for the bill presented by the rapporteur in the Chamber of Deputies, as well as some of the statements made by Congressmen during the debates in Parliament. Moreover, it also presents some data on trade unions in the post-reform period, from 2017 onwards, identifying that there has been a weakening of trade union entities, such as the withdrawal of the union tax without any transition period or adaptation rules and the creation of a series of new types of employee contracts, based on the ideal of individual freedom, which fragment the professional category and weaken the social solidarity that is indispensable for the strength of trade union action. Some cases analyzed by the Committee on Freedom of Association were examined in order to verify the interpretative parameter regarding the possibility of collective bargaining to reduce rights provided for by law, as well as statements made by the Committee of Experts specifically regarding the Labor Reform in the period from 2018 to 2023. In the end, the hypotheses were confirmed, in the sense that Law no. 13.467/2017 proved to be a true pro-business public policy, sought to weaken not only the legislation protecting human labor, but also the resistance structures of the working class, in addition to being incompatible with the ILO's understanding. Another important conclusion from a sociological point of view is that the centrality of work has long since lost ground in society to individual freedom under the political designs of neoliberalism. It was documentary and bibliographical research. The justification for the bill presented in the Chamber of Deputies and the Federal Senate were examined, as well as fragments of the deputies' debates using shorthand notes, all obtained from the Chamber of Deputies website. We also examined data on unions in the post-reform period already collected by REMIR – Network for Studies and Interdisciplinary Monitoring of Labor Reform, from the Unicamp Institute of Economics, and by CESIT – Center for Union Studies in Labor Economics, which It is made up of representatives from this Institute of Economics and DIEESE. The research had access to ILO documents from the years 1948, 1949, 1980 and 1981, regarding the preparatory acts for the adoption of ILO Conventions 98 and 154, which were obtained after requesting the ILO library through the email to library@ilo.org. The decisions of the Committee on Freedom of Association and the statements made by the Committee of Experts are data accessible through websites and documents published by the ILO, also accessible on the internet.